A review of Acalypha indica L. (Euphorbiaceae) as traditional medicinal plant and its therapeutic potential. (31st July 2017) - Zahidin, Nor Syahiran; Saidin, Syafiqah; Zulkifli, Razauden Mohamed; Muhamad, Ida Idayu; Ya'akob, Harisun; Nur, Hadi
Abstract: Ethnopharmacological relevance: Acalypha indica is an herbal plant that grows in wet, temperate and tropical region, primarily along the earth's equator line. This plant is considered by most people as a weed and can easily be found in these regions. Although this plant is a weed, Acalypha indica has been acknowledged by local people as a useful source of medicine for several therapeutic treatments. They consume parts of the plant for many therapeutics purposes such as anthelmintic, anti-ulcer, bronchitis, asthma, wound healing, anti-bacterial and other applications. As this review was being conducted, most of the reports related to ethnomedicinal practices were from Asian and African regions. The aim of the review: The aim of this review is to summarize the current studies on ethnomedicinal practices, phytochemistry, pharmacological studies and a potential study of Acalypha indica in different locations around the world. This review updates related information regarding the potential therapeutic treatments and also discusses the toxicity issue of Acalypha indica . Materials and methods: This review was performed through a systematic search related to Acalypha indica including the ethnomedicinal practices, phytochemistry and pharmacological studies around the world. The data was collected from online journals, magazines, and books, all of which were published in English, Malay and Indonesian. Search engine websites such as Google, Google Scholar, PubMed, Science Direct, Researchgate and other online collections were utilized in this review to obtain information. Results: The links between ethnomedicinal practices and scientific studies have been discussed with a fair justification. Several pharmacological properties exhibited certain potentials based on the obtained results that came from different related studies. Based on literature studies, Acalypha indica has the capability to serve as anthelmintic, anti-inflammation, anti-bacterial, anti-cancer, anti-diabetes, anti-hyperlipidemic, anti-obesity, anti-venom, hepatoprotective, hypoxia, and wound healing medicine. For the traditional practices, the authors also mentioned several benefits of consuming the raw plant and decoction. Conclusion: This review summarizes the current studies of Acalypha indica collected from many regions. This review hopefully will provide a useful and basic knowledge platform for anyone interested in gaining information regarding Acalypha indica . Graphical abstract: